Rekonstruksi Religiositas Etnik Melayu Dimensi Keyakinan pada Kitab dalam Puisi Melayu Tradisional - Roziah, Roziah (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2023)
The nature of being open to immigrants makes ethnic Malays exposed to various crimes such as fraud, physical violence, sexual violence, murder, theft, corruption, and the use of illegal drugs involving perpetrators who are Malay nationals or perpetrators who live in the Malay area, which continues to increase every year. the year. the year. This increase in crime rates shows that people in the Malay area are experiencing a decline in character. There have been various speculations that cultural customs, teachings, and advice on trust are no longer respected, or perhaps those who live in the Malay area have not been given teachings regarding the noble values of Malay culture, which are based on the Koran. Therefore, the dimension of religiosity related to Malay ethnic beliefs in the book needs to be reconstructed and internalized with the aim of strengthening Malay ethnic beliefs, and people living in Malay areas believe in the Koran as a guide to life. A descriptive qualitative study was completed through stylistic, semiotic, and hermeneutic approaches to traditional Malay poetry. The research data is in the form of rhymes, poetry, and expressions contained in Tenas Effendy's works. The data sources for the study come from four books. (1) Tunjung Ajar Melayu in Pantun Gurindam and Seloka; (2) Pantun Nasihat; (3) Syair Nasib Melayu; and (4) Tangkat Ajar Melayu: Details of Riau Malay Culture. Data was collected through reading, noting, and interpreting techniques, then coded to count the number of occurrences using the AnCont application. The validity of the data goes through a verification and validation process by experts in the fields of literature, Malay, and religion. Malay ethnic faith in the Koran appears in several categories, namely: (1) knowing God by devoutly reading the Koran; (2) Ethnic Malays use the Koran as Imam; (3) encouraging children to honor the Koran; (4) customary lines that are based on syarak and syarak based on the Book of Allah; (5) diligently listening to the reading of the Koran is believed to expand knowledge; (6) making the Koran a guide for life; and (7) diligently studying the Koran as a sign of Malay luck. The reconstruction of the religiosity dimension of belief in books shows that traditional Malay poetry is a literary work that contains a call to amar maruf nahi mungkar. It is hoped that this study can have implications for learning. Riau Malay culture in schools and oral literature in universities.